PENGARUH PEMBERIAN KADAR AIR BERBEDA TERHADAP PERTUMBUHAN DAN PRODUKSI HIJAUAN TANAMAN Indigofera zollingeriana - Ranti M. A. D.; N. N Suryani; I K. M. Budiasa (Jurnal Peternakan Tropika, 2017)
This study aimed to determine the water content suitable for plant growth and forage plant Indigofera zollingerianaproduction. The research was carried out for 15 weeks in Greenhouse Research Station Faculty of Animal Husbandry at Udayana University, Jalan Raya Sesetan, GangMarkisa Denpasar. The experimental design used was completely randomized design (CRD) with five treatments, they were: 100%, 90%, 80%, 70%, and 60% of field capacity with five replications. The results showed that the plant height and number of leaves were significant (P